RANGAIG TRANSFORMS BASED HAM FOR SOLVING SOME TWO- DIMENSIONAL PDES - Inderdeep Singh; Sandeep Sharma (Journal of Mechanics of Continua and Mathematical Sciences)
This research presents a formulation of a hybrid scheme for the approximate solution of “Two-Dimensional Partial Differential Equations” (PDEs) used in engineering applications and several scientific. This approach combines the “Rangaig Transform with the Homotopy Analysis Method (HAM)” to form an efficient and robust explanation technique. Thus, the idea of our hybrid scheme combines the advantages of both approaches to make it easier to solve the given PDE while maintaining the highest accuracy. Several numerical examples have been solved to demonstrate the suggested method, and the outcomes make it evident how straightforward and accurate the method is for handling such a challenging issue.